The prevalence of occupational asthma in auto and furniture dye workers in Elazig downtown - Turgut, Teyfik; Tasdemir, Canatan; Muz, M. Hamdi; Deveci, Figen; Kirkil, Gamze (Turkish Assoc Tuberculosis & Thorax, 2005)
Occupational asthma (OA) is characterized by reversible airway obstruction and/or bronchial hyperresponsiveness occurred after exposition to dust, vapor, gas or smoke which are present in the workplace. We aimed to determine the frequency of OA in auto and furniture dye workers in our city center. One-hundred-forty-two workers in Elazig Central Industrial Centre (86 auto, 56 furniture dyers) were included in the study. The workers were questioned with Turkish Thorax Association Occupational and Environmental Pulmonary Diseases Evaluation Form, and physical examination and pulmonary function tests (PFT) were performed. Follow of peak expiratory flow rate (PEFR) and reversibility tests were performed to patients who had complaints or abnormality in PFT. The workers who had reversibility and positive daily PEFR variability were taken away from work and PEFR variables were followed. The workers had no symptoms when they were taken away from work and daily PEFR were below than 20%, accepted as OA. Twenty-one workers of 22 workers who have abnormal questionnaire, symptoms and abnormality in PFT, accepted daily PEFR measurements. Daily PEFR variability and reversibility test were positive in 5 (3.52%) workers who were accepted as OA. We detected the prevalence of OA, an important worker health problem, was 3.52% in auto and furniture dyers in industrial centre of our city. We think that the prevalence of OA can be determined with detailed history, serial PEFR follow and using PFT, in the apsence of specific bronchial provocative tests. Thus, it is important to be become conscious about OA the groups who are under risk.
Keywords: Occupational asthma; pulmonary function tests; dye workers